Elementary sulfur or calcium sulfate to the remediation of saline-sodic soils? - Josinaldo Lopes Araujo (Pesquisa Agropecuária Tropical, 2015)
The recovery of soils with high salinity and alkalinity requires the use of products that decrease the pH and exchangeable sodium content, in order to improve their fertility. This study aimed at evaluating the effect of calcium sulfate and elementary sulfur on the chemical properties of a soil with high contents of soluble salts and exchangeable sodium. Two experiments were carried out in a greenhouse using samples of a sandy loam saline-sodic soil. In the first experiment, four soil correction treatments (without correction, without correction and washing, corrected with calcium sulfate, and corrected with elementary sulfur) were tested. In the second experiment, five elementary sulfur doses (0 kg ha-1, 400 kg ha-1, 800 kg ha-1, 1,200 kg ha-1 and 1,600 kg ha-1) were tested. The elementary sulfur and calcium sulfate positively affected the chemical properties of the soil, improving its fertility. The elementary sulfur, besides improving the soil chemical properties, is more efficient than calcium sulphate in decreasing alkalinity, however, the use of this product requires the application of additional calcium to the soil. Due to its low clay content, the simple washing process decreases soil salinity and sodicity.